(untitled) (Beacon: International Journal of Education and Social Studies, 2026)
This study examines the role of local culture integration in reducing the potential for religious-based social conflict in Indonesia. Using a quantitative approach, data were collected through surveys involving 1,000 respondents from 34 provinces selected by multi-stage random sampling. The analysis was conducted using descriptive statistics, correlation analysis, multiple regression, and significance testing to examine the relationship between cultural integration variables and conflict potential. The findings indicate that local cultural integration has a significant but relatively limited effect in reducing religious-based social conflict, contributing 5.7% of the variance. Among the examined variables, tolerance strengthening, cultural accommodation, and spiritual strengthening show the strongest negative and significant relationships with conflict indicators such as intolerance, perceived threat, and support for violence. However, some cultural dimensions such as personal development and environmental harmony are not statistically significant predictors. These results suggest that while local culture plays an important role as a social stabilizer, broader structural factors also influence conflict dynamics in plural societies. The study concludes that strengthening cultural accommodation and tolerance-based values is essential in maintaining social harmony in Indonesia, but it must be supported by economic, political, and institutional factors to achieve more comprehensive conflict prevention.